Сучасні підходи до активізації навчальної діяльності студентів технічних навчальних закладів - Перетяка, Наталія Олександрівна; Peretiaka, Nataliіa (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розглянуто метод проєктів як сучасний освітній інструмент для викладання фізики у коледжі. Показано його значення для формування дослідницьких компетентностей, розвитку критичного мислення та підвищення мотивації студентів. Проаналізовано класифікацію дослідницьких, практико-орієнтованих, інформаційних, творчих проєктів та запропоновано алгоритм їх організації: постановка проблеми, планування, виконання, презентація та оцінювання. Визначено переваги проєктного навчання – інтеграція знань, практична спрямованість, розвиток командної роботи. Надані рекомендації з організації проведення конкурсу проєктів з фізики. Окреслено основні переваги та недоліки впровадження методу проєктів. Практичне значення дослідження полягає у можливості використання запропонованих рекомендацій викладачами фізики для вдосконалення навчального процесу. /// EN: The article explores the project method as a modern pedagogical technology for teaching physics in technical colleges. It emphasizes the importance of project-based learning in developing students’ research competencies, critical thinking, motivation, and teamwork skills. The author presents a classification of projects – research, practice-oriented, informational, and creative – and proposes an organizational algorithm consisting of five stages: problem setting, planning, implementation, presentation, and evaluation. The study highlights the advantages of the project method, including knowledge integration, practical orientation, interdisciplinary connections, and the development of communication skills. The advantages of holding a physics project competition are indicated. At the same time, it identifies challenges such as limited technical resources, time constraints, and difficulties in evaluating group projects. To address these issues, the article suggests solutions based on digitalization, automation, and time management strategies. Special attention is given to the experience of Melitopol College of Dmytro Motornyi Tavria State Agrotechnological University, where project-based learning is actively implemented in physics courses. At the end of each section, students are encouraged to complete projects that consolidate knowledge and foster creativity. Moreover, the annual student project competition in physics is described as a powerful educational tool that promotes 21st-century competencies – critical thinking, creativity, communication, and collaboration. The article concludes that the project method is an effective instrument for activating students’ learning activities, combining theoretical knowledge with practical skills, and ensuring systematic development of professional competencies.
Modern approaches to enhancing the learning activity of students in technical educational institutions
Keywords: компетентності; метод проєктів; мотивація студентів; конкурс проєктів; фізика; competencies; project-based learning; student motivation; project competition; physics